IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Okta Reza, Nia; Wibowo, Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education plays a strategic role in developing students' character from the elementary school level. Amid globalization and rapid technological advancement, students face various challenges that may influence their attitudes, behaviors, and perspectives toward diversity. Issues such as low levels of tolerance, lack of empathy, bullying, and discriminatory attitudes toward differences in ethnicity, religion, culture, and language have become significant challenges that need to be addressed through meaningful learning experiences. Therefore, the implementation of Pancasila Education in elementary schools should be designed using contextual and student-centered learning approaches that integrate conceptual understanding with character development, enabling students to internalize Pancasila values in their daily lives. This study aims to describe the implementation of Pancasila Education in fostering students' character in elementary schools, identify the supporting and inhibiting factors affecting its implementation, and analyze teachers' strategies in instilling Pancasila values through classroom learning activities. The study employed a qualitative descriptive approach. The research participants consisted of a sixth-grade Pancasila Education teacher and students from an elementary school. Data were collected through classroom observations, in-depth interviews, and documentation. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The trustworthiness of the findings was ensured through source triangulation and methodological triangulation. The findings indicate that the implementation of Problem-Based Learning (PBL), group discussions, case studies, and character- strengthening projects effectively enhanced students' understanding of diversity, the meaning of national unity, and the application of Pancasila values in everyday life. In addition to improving critical thinking and problem-solving skills, these learning strategies successfully fostered tolerance, empathy, responsibility, cooperation, and teamwork among students from diverse cultural and social backgrounds. The success of the learning process was supported by teachers' professional competence, the use of innovative learning media, a conducive school environment, and strong support from school principals and parents. Meanwhile, the main obstacles included differences in students' characteristics, limited learning resources, and students' initial lack of understanding of diversity. Therefore, implementing innovative, contextual, and student-centered learning is an effective strategy for internalizing Pancasila values while strengthening character education among elementary school students.